Auditory-Somatosensory Temporal Sensitivity Improves When the Somatosensory Event Is Caused by Voluntary Body Movement - Kitagawa, Norimichi; Kato, Masaharu; Kashino, Makio (Frontiers in Integrative Neuroscience, 2016)
When we actively interact with the environment, it is crucial that we perceive a precise temporal relationship between our own actions and sensory effects to guide our body movements. Thus, we hypothesized that voluntary movements improve perceptual sensitivity to the temporal disparity between auditory and movement-related somatosensory events compared to when they are delivered passively to sensory receptors. In the voluntary condition, participants voluntarily tapped a button, and a noise burst was presented at various onset asynchronies relative to the button press. The participants made either 'sound-first' or 'touch-first' responses. We found that the performance of temporal order judgment (TOJ) in the voluntary condition (as indexed by the just noticeable difference) was significantly better (M=42.5 ms ±3.8 s.e.m) than that when their finger was passively stimulated (passive condition: M=66.8 ms ±6.3 s.e.m). We further examined whether the performance improvement with voluntary action can be attributed to the prediction of the timing of the stimulation from sensory cues (sensory-based prediction), kinesthetic cues contained in voluntary action, and/or to the prediction of stimulation timing from the efference copy of the motor command (motor-based prediction). When the participant’s finger was moved passively to press the button (involuntary condition) and when three noise bursts were presented before the target burst with regular intervals (predictable condition), the TOJ performance was not improved from that in the passive condition. These results suggest that the improvement in sensitivity to temporal disparity between somatosensory and auditory events caused by the voluntary action cannot be attributed to sensory-based prediction and kinesthetic cues. Rather, the prediction from the efference copy of the motor command would be crucial for improving the temporal sensitivity.